2021
DOI: 10.3390/nu13103493
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility and Efficiency of the BEFORE (Better Exercise and Food, Better Recovery) Prehabilitation Program

Abstract: Prehabilitation has been postulated as an effective preventive intervention to reduce postoperative complications, particularly for elderly patients with a relatively high risk of complications. To date, it remains to be determined whether prehabilitation increases physical capacity and reduces postoperative complications. The aim of this study was to assess the feasibility of a 4-week multimodal prehabilitation program consisting of a personalized, supervised training program and nutritional intervention with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
27
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(29 citation statements)
references
References 47 publications
2
27
0
Order By: Relevance
“…Among 20 available studies on prehabilitation for CRC patients, there are 10 randomized controlled trials (RCTs) [ 26 , 27 , 30 , 31 , 32 , 37 , 38 , 39 , 40 , 43 ], 9 pilot studies [ 16 , 17 , 29 , 33 , 34 , 35 , 36 , 41 , 44 ] and 1 retrospective cohort study [ 42 ]. Table 3 summarizes the reported outcomes of selected studies.…”
Section: The Present Concept Of Prehabilitation In Surgical Managemen...mentioning
confidence: 99%
See 4 more Smart Citations
“…Among 20 available studies on prehabilitation for CRC patients, there are 10 randomized controlled trials (RCTs) [ 26 , 27 , 30 , 31 , 32 , 37 , 38 , 39 , 40 , 43 ], 9 pilot studies [ 16 , 17 , 29 , 33 , 34 , 35 , 36 , 41 , 44 ] and 1 retrospective cohort study [ 42 ]. Table 3 summarizes the reported outcomes of selected studies.…”
Section: The Present Concept Of Prehabilitation In Surgical Managemen...mentioning
confidence: 99%
“…Studies included in this review showed that unimodal exercise prehabilitation consisting of aerobic and/or resistance exercises is a safe and viable option for CRC patients [ 29 , 30 , 31 , 33 , 34 , 35 , 40 , 41 , 43 ]. Additionally, it positively impacts fitness level (improved VO 2peak , 6-minute walking distance scores, functional walking capacity), leg (e.g., quadriceps), arm, and inspiratory muscle strength.…”
Section: The Present Concept Of Prehabilitation In Surgical Managemen...mentioning
confidence: 99%
See 3 more Smart Citations